L’immagine-gesto. Note su immaginazione, gestualità e cinema - Cecchi, Dario (Aesthetica Preprint, 2023)
The article reconsiders the relationship existing among perception, imagination and language within the filmic experience. To do so, it offers an interpretation of Emilio Garroni’s philosophy of the imagination, which was deeply influenced by the reading of Kant’s Critique of Judgment. It also compares Garroni’s thought with Maurice Merleau- Ponty’s essay on cinema, in which the reference to the third Critique seems also to play a key role. Hence emerges the idea that cinema is exemplarily able to disarticulate the intertwining of language and imagination, which enables the reference of meanings and concepts to reality. By doing so, cinema is likely to engender new forms of mediality, namely a renewed engagement with gesture, as states Giorgio Agamben. According to the latter, gesture is a form of ‘pure mediality’, as far as it epitomizes Kant’s concept of ‘finality with no end’. However, following Garroni, the article shows that the filmic gesture is able to display its medial import, because of the peculiar reorganization of the relationship between imagination and language that result from the filmic work.